Alfred Marshall: Victorian Relevance for Modern Economics - Levitt, Theodore (Quarterly Journal of Economics, 1976)
Introduction, 425.—The economy of children and family, 427.—Wages and distribution theory, 430.—Beyond economics, 432.—Moralizing and theorizing, 435.—Unfinished unintentions, 438.—The principles in Principles, 440.